2014
DOI: 10.1074/jbc.m113.507020
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization-induced Conformational Change in the C-terminal Region of Nel-like Molecule 1 (NELL1) Protein Is Necessary for the Efficient Mediation of Murine MC3T3-E1 Cell Adhesion and Spreading

Abstract: Background: NELL1, an oligomeric glycoprotein, is an osteoinductive factor. Results: The C-terminal cysteine-rich region of NELL1 has cell-binding activity. Intermolecular, but not intramolecular, disulfide bonding is important for the oligomerization and cell adhesion activity of NELL1. Conclusion: NELL1 requires oligomerization-induced conformational change for efficient mediation of cell adhesion and spreading. Significance: The structural basis of NELL1-mediated cell adhesion is identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The results showed that Nell-1 effectively activated the ERK and JNK pathways rather than the P38 pathway in pre-osteoblasts on Ti surfaces. Nakamura Y et al found that Nell-1 mediated cell adhesion by binding to integrin receptors to activate ERK in MC3T3-E1 cells [47], confirming that Nell-1 can activate the ERK pathway in pre-osteoblasts. Interestingly, the selective activation of different MAPK pathways by Nell-1 depends on cell type [26].…”
Section: Discussionmentioning
confidence: 86%
“…The results showed that Nell-1 effectively activated the ERK and JNK pathways rather than the P38 pathway in pre-osteoblasts on Ti surfaces. Nakamura Y et al found that Nell-1 mediated cell adhesion by binding to integrin receptors to activate ERK in MC3T3-E1 cells [47], confirming that Nell-1 can activate the ERK pathway in pre-osteoblasts. Interestingly, the selective activation of different MAPK pathways by Nell-1 depends on cell type [26].…”
Section: Discussionmentioning
confidence: 86%
“…62, 66 In contrast, prior studies have suggested that assembly of NELL-1 into homo-oligomeric structures is at least partially required for its bioactive effects. 67 Fourthly, the cost of manufacturing and risk of contamination can be considerably diminished by using small molecules. 62 Unfortunately, no known small molecule has yet been developed as an agonist for NELL-1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Preosteoblastic cells are precursor cells of mature osteoblasts, located in bone marrow stroma in high numbers, and likely to be critically affected by wear debris during the AL process. Several studies have used MC3T3‐E1 cells as a model of preosteoblasts for differentiation and functionality of osteoblastic cells …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used MC3T3-E1 cells as a model of preosteoblasts for differentiation and functionality of osteoblastic cells. 11,20 In this study, we first established the concentration range of particulate and ion forms of Co-Cr alloy that could effectively affect the functions of preosteoblasts without severe cytotoxicity in a 72-h culture. It appeared that particles 2.5 mg mL 21 or ions 500 lM resulted in significant cell death compared to debris-free controls, while particles 0.15 mg mL 21 or ions 32 lM did not show any influence on preosteoblasts.…”
Section: Discussionmentioning
confidence: 99%